Rod and cone contributions to horizontal cell light responses in the mouse retina. - HUMPHRIES, PETER (The Society for Neuroscience, 2008)
Mammalian B-type horizontal cells make contact with both photoreceptor types: the dendrites contact cone photoreceptors, whereas the axon terminal processes contact rods. Despite their distinct synaptic contacts, horizontal cell somata and axon terminals receive a mixture of rod and cone inputs. Interaction of the two photoreceptor systems is essential for adaptation of photoreceptor sensitivity to different levels of background illumination, and horizontal cells play a key role in this adaptation. In this study, we used transgenic mouse lines to examine the contributions of rod and cone photoreceptor inputs to horizontal cell light responses in the mouse retina: rod signals were isolated by recording intracellularly from horizontal cells in a mouse lacking the cone cyclic nucleotide-gated channel, which lacks cone function, and cone signals were assessed using the rhodopsin knock-out mouse, which is a model for pure cone function. We found that both horizontal cell compartments receive a mixture of inputs from both photoreceptor types. To determine whether these inputs arrive via the long axon connecting the compartments or by way of rod?cone gap junctional coupling, we assessed the rod and cone contributions to horizontal cell somatic and axon terminal light responses in the connexin36-deficient mouse retina, which lacks rod?cone coupling. Our results confirm that rods and cones are coupled by connexin36, and suggest that signal transmission along the axon is unidirectional: signals are passed from horizontal cell soma to axon terminal but not from axon terminal to soma.
PUBLISHED
Keywords: retina; horizontal cell; axon terminal; CNG; rhodopsin; connexin36